DJ stent - boon or curse? - Agrawal, AS; Rao, S; Gupta, AO (Journal of College of Medical Sciences-Nepal, 2014)
DJ stent is considered as a boon by the urologist but without proper knowledge it turns to be curse for the patient. We report a case of a 34 year old man who developed vesical calculus secondary to DJ stent in a short span of 6-8 months. He underwent cystolithotomy for removal of the vesical calculus along with the DJ stent. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-3, 55-59 DOI: http://dx.doi.org/10.3126/jcmsn.v9i3.10224